Using Interactive Games for the Teaching of Question Tags: Insights from an English Language Course In Indonesia - Meiva Eka Sri Sulistyawati; Lady Diana Warpindyastuti (Universitas Islam Negeri (UIN) Mataram, 2018)
Learning foreign language has been the part of our educational systems. It has been taught from the early stage of education. However, there are still many difficulties in learning. And there are many challenges for the teachers to make it as a fun learning. This research aims is examine how can the interactive games can help the students to understand about questions tags better and can be used in the daily conversation. Meanwhile, the observed population that was used for the research was the students of English For All (EFA) English Course in Cirendeu, Tangerang Banten. The students were Junior High School students. The writers used the descriptive qualitative methods as using interactive games which was using oral test and conversation activities to learn how much their improvement in understanding about question tags. Keywords: Question Tags, Interactives Games, Teaching